Dimethylglycine supplementation in horses performing incremental treadmill exercise - de Oliveira, K. [UNESP]; Fachiolli, D. F. [UNESP]; Watanabe, M. J. [UNESP]; Tsuzukibashi, D. [UNESP]; Bittar, C. M.M.; Costa, C. [UNESP]; Poiatti, M. L. [UNESP]; Meirelles, P. R.L. [UNESP] (Brill Academic Publishers, 2015)
Our objective was to verify the effect of the period of dimethylglycine (DMG) supplementation in horses subjected to incremental treadmill exercise, on the metabolic and physiologic variables and indices related to physical performance. Four adult Arabian horses with a mean age of 8±1.5 years and a mean body weight of 340±10.8 kg were used. The utilised experimental design was the 4×4 Latin square, constituted by four periods of four weeks of evaluation, intercalated with four weeks of wash-out periods. The treatments consisted of periods of DMG (30 g of commercial product) administration: without supplementation, and with supplementation for 10, 20 and 30 days. There was a significant effect of the DMG supplementation given during 30 days over the reduction in the lactate concentration after the test exercise. Alterations of V200 (speed in which the horse reaches 200 heart beats/min) and VL4 (speed which corresponds to a blood lactate of 4 mmol/l) were not observed (P>0.05), however there was a travelled distance elevation in the tests in function of the increase on the days of supplementation, by linear regression (P<0.05) analysis. It was verified that there was no effect from the DMG supplementation in horses on the heart rate and there was only a significant difference between treatments for the rectal temperature after exercise, where the supplementation for 30 days resulted in values statistically superior to the control group. Therefore, we can conclude that the equine supplementation with a DMG product in the dosage of 30 g/day for a one-month period affects the lactate metabolisms, as well as increases the travelled distance during an incremental treadmill test.
Keywords: Equine; Ergogenic; Lactate; Physical activity